Strategic Infrastructure Transformation: Revolutionizing Financial Sector Management for Enhanced Success - Koldovskiy Artem; Koldovszkij A.; Колдовський Артем (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2024)
Abstract. This article explores the transformative landscape of strategic infrastructure within the financial sector, focusing on the dynamic interplay between technology integration and human capital in shaping operational efficiency. The introduction outlines the problem statement, emphasizing the growing significance of strategic infrastructure in financial management. Leveraging an advanced econometric model, our research unveils crucial insights into the predictors of operational efficiency. The results showcase the substantial influence of both technology integration and human capital on operational efficiency, with coefficients of 0.89 and 1.15, respectively. These findings underscore the critical role that technological advancements and investment in human capital play in optimizing operational performance within financial institutions. The model's high Multiple R-squared (0.82) and Adjusted R-squared (0.80) values affirm its effectiveness in explaining approximately 80% of the variability in Operational Efficiency. Furthermore, the overall significance of the model is established by a robust F-statistic (36.45) and a low Prob (F-statistic) value (< 0.001). The model's goodness of fit is supported by lower Akaike information criterion (AIC) and Bayesian information criterion (BIC) values (456.78 and 468.12, respectively), striking a balance between accuracy and complexity. The discussion of results delves into the practical implications for decision-makers in financial institutions, emphasizing the need for a harmonious integration of technology and human capital strategies. These insights provide a valuable foundation for enhancing strategic management practices within the financial sector. In conclusion, this article contributes to the scientific novelty by employing an innovative blend of theoretical frameworks, empirical data, and advanced econometric modeling. The synthesized results offer a clear and logical presentation of influential factors, model effectiveness, and practical implications. As the financial landscape continues to evolve, the implications of this research extend beyond the current study, opening avenues for future investigations into the nuanced dynamics of strategic infrastructure transformation.

Ez a cikk a pénzügyi szektor stratégiai infrastruktúrájának átalakulását vizsgálja, kiemelve a technológia és a humán tőke integrációja közötti dinamikus kölcsönhatást a működési hatékonyság alakításában. A bevezetés a stratégiai infrastruktúra növekvő jelentőségének kiemelésével teremti meg a terepet a pénzügyi irányításban. Egy kifinomult ökonometriai modell segítségével tanulmányunk kulcsfontosságú betekintést nyújt a műveletek előrejelző teljesítményébe. Az eredmények azt mutatják, hogy mind a technológiai integráció, mind a humántőke jelentős hatást gyakorol a műveletek hatékonyságára, 0,89-es, illetve 1,15-ös koefficiensekkel. Ezek az eredmények kiemelik a technológiai fejlődés és a humántőke-befektetések kritikus szerepét a műveletek hatékonyságának optimalizálásában a pénzügyi intézményekben. A modell magas többszörös Rnégyzet (0,82) és kiigazított R-négyzet (0,80) értékei megerősítik, hogy a modell hatékonyan magyarázza a működési hatékonyságban mutatkozó eltérések mintegy 80%-át. A modell általános szignifikanciáját továbbá erős F-statisztikája (36,45) és alacsony Prob (F-statisztika) értéke (< 0,001) is megerősíti. A modell megfelelőségét az Akaike-kritérium (AIC) és a Bayes-kritérium (BIC) alacsony értékei (456,78 és 468,12) is alátámasztják, egyensúlyt teremtve a pontosság és a bonyolultság között. Az eredmények megvitatása mélyen belemerül a pénzügyi intézmények döntéshozatalára vonatkozó gyakorlati következményekbe, hangsúlyozva a technológiai és humánerőforrás-stratégiák harmonikus integrációjának szükségességét. Ezek a meglátások értékes alapot nyújtanak a pénzügyi szektor stratégiai irányítási gyakorlatának javításához. Összefoglalva, a tanulmány eredményei hozzájárulnak a pénzügyi szektor irányításáról szóló tudományos vitához azáltal, hogy koherens képet nyújtanak az elméleti szempontokról és az empirikus eredményekről. Az eredmények megalapozott döntéshozatalt tesznek lehetővé, és meghatározzák a további kutatások irányát a pénzügyi szektor stratégiai infrastruktúra átalakításának dinamikus táján.

Резюме. Ця стаття досліджує трансформаційний ландшафт стратегічної інфраструктури в фінансовому секторі, акцентуючи динамічну взаємодію між інтеграцією технологій та людським капіталом у формуванні ефективності операцій. Вступ намічає проблематику, підкреслюючи зростаючу значущість стратегічної інфраструктури в фінансовому управлінні. Використовуючи високорозвину економетричну модель, наше дослідження розкриває ключові уявлення про передбачувані показники ефективності операцій. Результати показують суттєвий вплив як інтеграції технологій, так і людського капіталу на ефективність операцій, з коефіцієнтами відповідно 0.89 та 1.15. Ці висновки підкреслюють критичну роль технологічних досягнень та інвестицій у людський капітал у оптимізації ефективності операцій у фінансових установах. Високі значення Multiple R-squared (0.82) та Adjusted R-squared (0.80) моделі підтверджують її ефективність у поясненні приблизно 80% варіативності ефективності операцій. Більше того, загальна значущість моделі підтверджується міцним F-статистиком (36.45) та низьким значенням Prob (F-статистики) (< 0.001). Достатню адаптацію моделі підтримують низькі значення критерію Акаіке (AIC) та критерію Байєса (BIC) (відповідно 456.78 та 468.12), забезпечуючи баланс між точністю та складністю. Обговорення результатів глибоко вдається у практичні наслідки для прийняття рішень у фінансових установах, акцентуючи необхідність гармонійної інтеграції стратегій технологій та людського капіталу. Ці уявлення становлять цінний фундамент для вдосконалення стратегічних практик управління в фінансовому секторі. Підсумовуючи, отримані з дослідження висновки вносять свій внесок в наукову дискусію про управління фінансовим сектором, надаючи згуртований погляд на теоретичні аспекти та емпіричні результати. Отримані висновки надають підґрунтя для обґрунтованого прийняття рішень та визначають напрямок подальших досліджень у динамічному ландшафті стратегічної інфраструктурної трансформації в фінансовому секторі.
Az infrastruktúra stratégiai átalakítása: a pénzügyi szektor irányításának forradalmi átalakítása a teljesítmény javítása érdekében
Cтратегічна трансформація інфраструктури: революція управління фінансовим сектором для підвищення успішності
Редакційна колегія: https://aab-economics.kmf.uz.ua/aabe/about/editorialTeam
Зміст: https://aab-economics.kmf.uz.ua/aabe/issue/view/5
Keywords: infrastructure; strategic transformation; financial sector; management; revolutionizing; enhanced success